Ripe : a novel - Etter, Sarah Rose (Scribner, 2023)
"A year into her dream job at a cutthroat Silicon Valley startup, Cassie finds herself trapped in a corporate nightmare. Between the long hours, toxic bosses, and unethical projects, she also struggles to reconcile the glittering promise of a city where obscene wealth lives alongside abject poverty. Ivy League grads complain about the snack selection from a conference room with a view of houseless people bathing in the bay. Startup burnouts leap into the paths of commuter trains and men literally set themselves on fire in the streets. Though isolated, Cassie is never alone. From her earliest memory, a miniature black hole has been her constant companion. It feeds on her depression and anxiety, its size changing in relation to her distress. The black hole watches, but it also waits. Its relentless pull draws Cassie ever-closer as the world around her unravels. When her CEO's demands cross an illegal threshold and she ends up unexpectedly pregnant, Cassie must decide whether the tempting fruits of Silicon Valley are really worth it. Sharp but vulnerable, funny yet unsettling, Ripe portrays one millennial woman's journey through our late-capitalist hellscape and offers a brilliantly incisive look at the absurdities of modern life"--